The determinants of preference for healthcare facilities in Calapan City, Oriental Mindoro - Santos, Vicente Jeronimo L. (Manila College of Public Health, University of the Philippines Manila, 2011)
Hospital administrators need to be aware of the healthcare needs of the clients and their preferences. This requires quality healthcare information to provide, preserve and expand healthcare services. Thus, this paper explored the Calapeños health economy to identify its influential determinants of preferences in choosing healthcare facilities.

Three-hundred-seventy-six (376) households were stratified-randomly selected in twenty (20) barangays at Calapan City. A descriptive design was implemented using a valid questionnaire to explore the healthcare preference among Calapeños. The survey was conducted from 13th to 30th of May 2010 and the gathered data were statistically analyzed using percentage distribution, mean, standard deviation, and multiple regression.

The findings reveal that the Calapeños health economy is composed of more young and middle-aged catholic males. Majority of the populace are non-working and have attained high-school level. The family size is usually four (4) to five (5) with an average monthly income of ₱10,000 and below. Furthermore, there are also significant relationships that existed between the Calapeños profile with patient factors (lifestyle pattern (r=0.24), perceived image of the healthcare provider (r=0.20), priorities in life (r=0.33), and existing culture and tradition (r=0.43)) and preference factors (accessibility (r=0.20), availability (r=0.34), and quality of service (r=0.21)). Further, significant relationship is present between preference factors and patient factors (availability (r=0.32), quality of services (r=0.19), and (3) perceived reliability of health care services (r=0.31)).
In a Calapeños health economy, both patient and preference factors affect the choice for healthcare facilities as perceived by the respondents. Educational attainment and lifestyle have significant influence over the healthcare preferences. Thus, healthcare services require to consider the clientele’s educational background and lifestyle with focus on quality and reliable services that are readily available to increase healthcare preference.
Includes bibliography.
Thesis
Keywords: Medical care -- Patient satisfaction -- Philippines -- Calapan City; Healthcare facilities -- Philippines -- Calapan City